Initiation-Response-Feedback Interaction in Reading of Narrative Text during Online Class Grade VIII in SMP Gajah Mada - Sarah Wahyuni Barasa (MultiTech Publisher, 2023)
This study was about Initiation-Response-Feedback Interaction in Reading of Narrative Text During Online Class Grade VIII In SMP Gajah Mada. The aims of the study was to state clearly the objectives of the study which is related with the problem of the study according to the IRF pattern. The Objectives is to describe what types and how IRF pattern in the classroom interaction in Reading narrative text was. The descriptive qualitative method was used in this study. Three methods were used to acquire data, those are: observation, video recording and interviewing. the subject of this study was students in 8th grade of SMP Gajah Mada. The data was examined using Sinclair and Coulthard theory in 1975. The result of this study were the following (1) The type of IRF pattern used in classroom interaction in Online Class based on Sinclair and Coulthard 1975 is used all, such as: Initiation, Response, and Feedback. (2) The realization of the IRF pattern itself already used in the classroom. Teacher always start the conversation in the class with Inititiation, as the first way to get students Responses, after teacher get responses from the students, teacher will give some feedback whether is it correct or no. In the classroom, both the teacher and the students employed unbalanced language. Only 37% teacher and students use English, while 63% use Bahasa. It is suggested to English teacher who taught all the topics, especially in Reading Narrative text to stimulated students to use English in the classroom. It is suggested for the students to improve their ability by have some extra effort to learn many vocabularies future.